Comparison of the clinical outcomes of non-invasive ventilation by helmet vs facemask in patients with acute respiratory distress syndrome. Issue 4 (29th January 2021) - Khatib, Mohamad Y.; Peediyakkal, Mohamed Z.; Elshafei, Moustafa S.; Elzeer, Hani S.; Ananthegowda, Dore C.; Shahen, Muhsen A.; Abdaljawad, Wael I.; Shaik, Karimulla S.; Kannappilly, Nevin; Mohamed, Ahmed S.; Soliman, Ahmed A.; Nashwan, Abdulqadir J.
Abstract : Abstract: The main aim of this study is to compare the use of non-invasive ventilation (NIV) via helmet versus face mask where different interfaces and masks can apply NIV. However, some of the limitations of the NIV face mask were air leak, face mask intolerance, and requirement of high positive end expiratory pressure, which could be resolved with the use of the helmet NIV. NIV facemask will be applied as per the facial contour of the patient. NIV helmet is a transparent hood and size will be measured as per the head size. Both groups will have a standard protocol for titration of NIV. Patients aged more than 18 years old and diagnosed with acute respiratory distress syndrome as per Berlin definition will be enrolled in the study after signing the informed consent. Subjects who met the inclusion criteria will receive 1 of the 2 interventions; blood gases, oxygenation status [Po2/Fio2] will be monitored in both groups. The time of intubation will be the main comparison factor among the 2 groups. The primary and secondary outcomes will be measured by the number of patients requiring endotracheal intubation after application of helmet device, Improvement of oxygenation defined as PaO2/FiO2 ≥ 200 or increase from baseline by 100, duration of mechanical ventilation via an endotracheal tube, intensive care unit length of stay, death from any cause during hospitalization at the time of enrolment, need for proning during the hospital stay, intensive care unit mortality, and the degree to which overt adverse effects of a drug can be tolerated by a patient including feeding tolerance. Trial registration number: NCT04507802. Protocol version: May 2020